Pengembangan Usaha Jasa Ransoe Konveksi Melalui Inovasi Dan Kreatifitas Penciptaan Produk Berbasis Customer Needs - Tambunan, Sarah Rouli; Rismawati, Rismawati; Surbakti, Enda Yunita; Haro, Jamardua (Politeknik Negeri Medan, 2023)
The conveyance service business is a dynamic industry where there are changing trends every year. This is what underlies Ransoe Konveksi's efforts to develop its production, especially to expand market share. However, the lack of specific skills of the employees has hampered the plan to make the latest products that are actually in great demand by the community. Therefore, the Polmed Service Team took the initiative to provide training to Ransoe Konveksi employees who would later be guided by professionals in their fields. If the employees' abilities are qualified to create new products that are in demand by the community, the convection services will be increasingly recognized by many people and will increase income.